Akselerasi Locus Delecti dan Tempus Delicti ‎ dalam Nalar Fikih Jinayah - Achmad Yasin (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2008)
The purpose of the application of the principle of locus delicti and tempus delicti in the enactment of criminal law is to safeguard the existence and provide the determinacy of law as well as justice for all citizens before the (criminal) law as the implementation of the equality before the law principle. The enforcement of criminal law embraces the principles of national jurisdiction, personal, legal protection and universal. The four principles have to be proportionally implemented with firmness, swiftness. They also have to comply with human rights and are free for intervention of the regime in power. The acceleration of locus delicti and tempus delicti equipped with the four principles is aimed at ensuring certainty of law (rechiszaherheid). In the perspective of Islamic criminal law (fiqh al- jinayah), the application of locus delicti and tempus delicti is fundamental duty in law enforcement which is an implementation of the purpose of Islamic law (maqasid al-shari’ah), which is to realize public welfare (jalb al-masalih) and preventing from harms (daf’ al-mafasid). The application of locus delicti and tempus delicti in Islamic law is meticulous, rigid and efficient because historically the Qur’anic verses and Prophetic Traditions on criminal law were revealed and implemented instantly during the prophet was still alive. It is also in line with the basis of Indonesia as a (rechtsstaats) that implement rule of law so that it considered a nomocracy. Such notion is evidenced with the enforcement of criminal law referring to Criminal Code (KUHPidana), Criminal procedure Code (KUHAPidana) as well as other organic laws.